LEVERAGING CHICKEN GROWTH SIMULATION PROGRAM (CGS) TO ENHANCE POULTRY PRODUCTION IN ANAMBRA STATE (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
The present study aims to investigate the effectiveness of a Chicken Growth Simulation Program as an educational tool in the field of poultry production. The research was conducted at a poultry farm in Umunze Community, Anambra State, with students enrolled in the Federal College of Education Technical, Umunze as primary participants. The study adopted a pre- and post-test approach. The study integrated the simulation program into the curriculum and measured its impact on students’ interest in poultry production. The t-test analysis performed on the data indicates that the treatment group showed a significant improvement in interest in poultry production compared to the control group (p < 0.05). Students exposed to contemporary technology demonstrated a deeper understanding and engagement with poultry management. The results of this study could have significant implications for both education and poultry production, potentially leading to curriculum development changes, enhanced learning experiences, and growth in the poultry industry.